Ceratophila, a new genus of erotylid beetles (Erotylidae: Pharaxonothinae) inhabiting male cones of the cycad Ceratozamia (Cycadales: Zamiaceae) - Tang, William; Skelley, Paul; Pérez-Farrera, Miguel Angel (Zootaxa, 2018)
Ceratophila new genus (Erotylidae: Pharaxonothinae) inhabiting male cones of the Mesoamerican cycad genus Ceratozamia Brongniart (Zamiaceae) is described for seven new species and compared to other genera of the Pharaxonothinae. Ceratophila differs from other genera of the Pharaxonothinae in many characters, most notable of which are: lateral pronotal carina thicker anteriorly in lateral view; head with supraocular and transverse occipital lines; elytra lacking a basal bead; and stridulatory files at base of head narrowly separated. Ceratophila has the male genitalia laterally compressed with a short median lobe and flagellum, similar to other Erotylidae. In comparison, the most superficially similar pharaxonothine genus Pharaxonotha Reitter has: lateral pronotal carina thin along entire length; head lacking supraocular lines, but with transverse occipital lines; elytra with distinct basal bead; stridulatory files at base of head widely separated; and unique male genitalia that are dorsoventrally flattened with a long median lobe and flagellum. Ceratophila contains two subgenera, which differ most notably in external characters and sexual dimorphism. Members of Ceratophila (Ceratophila), the nominal subgenus, have: more cylindrical bodies, pronotum evenly convex dorsally; the pronotum lacking basal longitudinal grooves on disc; metatibiae that are distinctly triangularly dilated toward apex; and no apparent external sexual dimorphism. In comparison, members of Ceratophila (Vovidesa) new subgenus have: dorsoventrally flattened bodies; the pronotum explanate (concave) along lateral margins; the pronotum with basal longitudinal grooves on disc; metatibiae weakly or not dilated toward apex; and with all tibiae in males showing strong sexual dimorphism. Four new species are described within the subgenus Ceratophila: C. (C.) chemnicki, C. (C.) gregoryi, C. (C.) picipennis, C. (C.) sanchezae; and three new species are described within the subgenus Vovidesa: C. (V.) chiapensis, C. (V.) mixeorum, C. (V.) vazquezi. Keys to genera, subgenera and species of known adults based on morphology are provided.